A multidisciplinary, phased nursing strategy for skin and mucosal management in a pediatric case of toxic epidermal necrolysis with respiratory failure: a case report - Yang, Cheng; Wen, Yang; He, Peijin; Dong, Yanling; Feng, Yunjie (Frontiers in Pediatrics, 2026)
IntroductionToxic Epidermal Necrolysis (TEN) is a life-threatening dermatologic emergency, with particularly high morbidity and mortality in children due to their vulnerable skin barrier and propensity for systemic complications. When TEN is further complicated by respiratory failure, the competing demands of airway management and skin preservation pose a significant therapeutic challenge.Case reportWe report a case of a 6-year-old boy with TEN involving 70% body surface area and concurrent respiratory failure. The patient required endotracheal intubation and mechanical ventilation, which exacerbated facial skin injury. A structured, multidisciplinary, and phased nursing protocol was implemented, integrating respiratory support with meticulous skin, ocular, oral, and urogenital care.Interventions & outcomesA coordinated team comprising pediatric intensive care, dermatology, infectious diseases, and nutrition specialists guided management. Skin care was staged according to wound healing phases, utilizing non-adhesive dressings, topical recombinant bovine basic fibroblast growth factor (bFGF) gel, and innovative tube-securement techniques. Systemic and mucosal care protocols were rigorously applied. The patient achieved complete re-epithelialization by day 35, was successfully extubated, and discharged in stable condition on day 46 with no major sequelae.ConclusionThis case demonstrates that a structured, phase-based, and multidisciplinary nursing approach can effectively balance life-sustaining interventions with tissue preservation in severe pediatric TEN. The strategy highlights the importance of adaptive wound staging, trauma-minimizing techniques, and proactive mucosal protection, offering a replicable framework for similar critical care scenarios.